2018
DOI: 10.1016/j.jfda.2017.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive polyphenols in kinkéliba tea ( Combretum micranthum ) and their glucose-lowering activities

Abstract: Herbal tea kinkéliba prepared from the leaves of Combretum micranthum has been widely consumed in West African countries for its flavor, nutritional and medicinal properties. Under bio-guided screening, the kinkéliba leaves were chemically investigated using various chromatographic and spectrometric methods that led to the identification of thirteen different flavonoid compounds. Further biological tests illustrated that the identified compounds may have synergistic effects to decrease the expression of phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 31 publications
1
45
0
2
Order By: Relevance
“…In this study, the chemical constituents isolated and identified from C. micranthum , pharmacological activities exhibited by the isolated compounds and the crude plant extracts were searched across Medline, Science Direct databases, web of science, PubMed and Google Scholar. Many authors had proved the presence of phenols (flavonoids and tannins) [62, 69, 70]. Our results corroborate these previous findings.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, the chemical constituents isolated and identified from C. micranthum , pharmacological activities exhibited by the isolated compounds and the crude plant extracts were searched across Medline, Science Direct databases, web of science, PubMed and Google Scholar. Many authors had proved the presence of phenols (flavonoids and tannins) [62, 69, 70]. Our results corroborate these previous findings.…”
Section: Discussionsupporting
confidence: 92%
“…In vitro bioassays have shown that the identified compounds may have synergistic effects to reduce glycemia. An additional in vivo study in C57BL/6J mice indicates that C. micranthum can reduce plasma glucose levels in a dose-dependent manner without significant weight loss or toxicity [62]. These in vitro and in vivo experiments support a potential new application of C. micranthum leaves as an antidiabetic agent.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Vitexin and isovitexin are considered to be the major leaf flavonoids 6 linked to the hypotensive activity of the plant 7 . More recently Chika 8 and Welch 9 demonstrated the potential antidiabetic property of Combretum micranthum leaves.…”
Section: Introductionmentioning
confidence: 99%
“…5 In another recent work, chlorogenic acids extracted from chicory were also shown to suppress hepatic glucose production. 9 The bulbs of the Easter lily, Lilium longiflorum Thunb., are widely used in Asian cooking and in traditional medicinal treatments. In China and Japan, the bulbs are added to culinary dishes and are also prescribed to treat inflammation, suppress coughing fits, and induce wound healing.…”
Section: Introductionmentioning
confidence: 99%